1993
DOI: 10.1007/bf00932238
|View full text |Cite
|
Sign up to set email alerts
|

Comparable seropositivity for ascariasis and toxocariasis in tropical slum children

Abstract: The seropositivities for infection by Ascaris lumbricoides and Toxocara canis were determined in children (1-15 years old) of a slum area of Caracas, Venezuela, and the levels that indicate the presence of active infection were defined. In children aged from 1 to 3 years, approximately 10% were positive for either parasite, and this figure increased to about 30% in 4- to 6-year-olds. For toxocariasis, the percentage of positivity remained at this level up to the age of 15 years. Whilst the positivity in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
2
8
0
3
Order By: Relevance
“…A similar trend was described from a survey of 669 individuals aged between 5 to 24 years old in Jordan (35). The same sera-positivity in children over 10 years old, were also recorded, by Lynch et al (36). In general, in T. canis the rate of infection tends to increase with age (37).…”
Section: Discussionsupporting
confidence: 76%
“…A similar trend was described from a survey of 669 individuals aged between 5 to 24 years old in Jordan (35). The same sera-positivity in children over 10 years old, were also recorded, by Lynch et al (36). In general, in T. canis the rate of infection tends to increase with age (37).…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, native T. canis ES antigens have been shown to cross-reacted with various helminth infections. 7,12,16,17,20,30 It has also reported that the prevalence rates are affected by the socioeconomic strata of the population examined. 24,27 Serologic tests based on an ELISA showed that 26 (12.1%) of 215 subjects showed positive reactions against the recombinant T. canis antigen and at least 19 of 26 individuals were infected with A. lumbricoides, T. trichiura, hookworms, and other parasites (Table 1).…”
Section: Prevalence Of Toxocariasis In Northeastern Brazilmentioning
confidence: 99%
“…7,[9][10][11][12][13][14] However, it has been shown that ES antigens are cross-reactive against serum samples from patients with a variety of helminth infections. 7,12,[15][16][17][18] Therefore, to overcome such problems, a recombinant T. canis antigen has been developed 18 and its high specificity and usefulness have been demonstrated. 19,20 In Brazil, seroepidemiologic studies on human toxocariasis have been carried out in Recife, Pernambuco, 21,22 Butantã, São Paulo, 23,24 Vitória, Espírito Santo, 25 Campinas, Sã o Paulo, 26 and Brasilia, Distrito Federal, 27 and it has been reported that the prevalence rates of toxocariasis reached approximately 40% in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…Since the studies made by SAVIGNY 37 , the antigens mostly used for the immunodiagnostic tests are excreted products derived from larvae cultivated in vitro and are referred to as Toxocara excretory/secretory (TES) antigens 35 , 37 . Nematode excretory/secretory (E/S) antigens are not species or genus specific and serum samples from patients with ascariosis, filariosis and strongyloidiosis show cross-reactivity with ES from T. canis and A. suum antigens when using enzyme-linked immune assay (ELISA), immunoprecipitation and Western blotting 3 , 5 , 18 , 20 , 21 , 29 , 37 . A major concern is the specificity of the ELISA and WB diagnosis of T. canis and A. suum in areas where gastrointestinal nematode infections of humans also exist.…”
Section: Introductionmentioning
confidence: 99%